Determinants of knowledge, attitudes, and practice towards sickle cell disease in Alebtong district, Lango region, Northern Uganda - Peninah Agaba; Olivia Nankinga; Candia Douglas Andabati; Euniky Musiimenta; Tracy Nagawa (BMC Public Health)
Abstract Background Sickle cell disease (SCD) is a debilitating hereditary medical condition associated with pain, stigma, morbidity, and early death. To reduce the prevalence and improve the quality of life of persons with SCD, improved knowledge, practices and reduced stigma are key for Uganda since improved medical breakthroughs in SCD diagnosis, care, and management are expensive in Uganda. However, there is limited research on knowledge, attitudes, and practice (KAP) towards SCD, therefore this study presents the levels and determinants of SCD KAP in Alebtong district, Lango region in Northern Uganda. Methods Data was obtained from 500 respondents aged 18 years and above in three sub-counties in Alebtong district. Multinomial logistic regression was used to identify key determinants of one’s knowledge and attitudes toward SCD. Binary logistic regression model was used to find the key determinants of SCD practices in Alebtong district. Results More than half of the respondents had good knowledge of SCD (60.8%) and good attitudes (87.0%). However, a very small percentage had ever tested for SCD (4.4%). The highest proportion of the respondents had a fair knowledge of SCD (49.6%) and good attitudes (82%). However, a very small percentage had ever tested for SCD (4.4%). Factors significantly associated with knowledge of SCD were residence, the commonest health information channel, and listening to the radio. Urban residents and those who mostly received their health information from community announcers were less likely to have a fair knowledge of SCD. Still, urban residents, those who mostly received their health information from community announcers, and those who never listened to the radio at all were less likely to have good knowledge of SCD. Respondents who listened to the radio less than once a week and those who never listened to the radio at all were less likely to have good attitudes toward persons with SCD. Respondents who completed primary education were more likely to test for SCD (aOR = 8.2, p = 0.05, 95%CI = 1.01–66.4). Conclusion Respondents had relatively high levels of good knowledge and attitudes towards SCD, but few had tested for SCD. This was significantly associated with access to information either through school, radio, or health providers. Communities, researchers, healthcare programmers, and policymakers should prioritize health information availability through different media to increase knowledge, attitudes, and practice toward SCD.